2020
DOI: 10.1111/ibi.12849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GPS tagging on behaviour and marine distribution of breeding Arctic Terns Sterna paradisaea

Abstract: Tracking tags have been used to map the distributions of a wide variety of avian species, but few studies have examined whether the use of these devices has impacts on the study animals that may bias the spatial data obtained. As Global Positioning System (GPS) tags small enough for deployment on terns (family: Laridae) have only recently become available, until now tracking of this group has been conducted by following unmanipulated individuals by boat, which offers a means of comparing distributions obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
0
21
1
Order By: Relevance
“…The total area across which arctic terns foraged (average 95% isopleth area) was 16-218 times larger than reported by Robertson et al (2014b) who tracked terns visually. Visually tracking arctic terns in boats appears to lead to smaller utilisation distributions than studies using tracking devices (Seward et al, 2020). However, arctic terns carrying GPS tracking devices in the Skerries, Wales also had smaller mean estimated home ranges (half to one fortieth of those recorded in this study) (Seward et al, 2020).…”
Section: Foraging Behaviourcontrasting
confidence: 48%
See 2 more Smart Citations
“…The total area across which arctic terns foraged (average 95% isopleth area) was 16-218 times larger than reported by Robertson et al (2014b) who tracked terns visually. Visually tracking arctic terns in boats appears to lead to smaller utilisation distributions than studies using tracking devices (Seward et al, 2020). However, arctic terns carrying GPS tracking devices in the Skerries, Wales also had smaller mean estimated home ranges (half to one fortieth of those recorded in this study) (Seward et al, 2020).…”
Section: Foraging Behaviourcontrasting
confidence: 48%
“…It is likely that the distances and home ranges that we report here reflect the space use of arctic terns breeding elsewhere in Iceland as Seward et al (2020) reported that the home ranges of GPS tagged and non-GPS tagged arctic terns were comparable. Indeed, if there is an effect of carrying the device on the birds (Geen et al, 2019;Tomotani et al, 2019), we might expect other arctic terns to travel even further without the burden of a tracking tag.…”
Section: Foraging Behaviourmentioning
confidence: 64%
See 1 more Smart Citation
“…Nevertheless, we recommend that researchers invest time in designing means of empirically examining the impact of tagging devices (e.g. Cleasby et al., 2020; Evans et al., 2020; Seward et al., 2020). Researchers will have to decide which impacts are most relevant to their study species and over what time period such effects will manifest themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Tags were attached, under licence, by trimming body feathers from the mantle, just posterior to the chestnut mantle band, and supergluing the tag with a muslin base directly to the skin and the 1-2-mm remainder of the trimmed feather shafts. This attachment method was an adaptation of that used by Seward et al (2020). The combined additional weight of metal ring, colour ring, tag, muslin and glue was on average ∼26 ± 0.4 g, which equated to less than 3% of the body mass of each bird (1142.5 ± 197.1 g).…”
Section: Fieldwork Methodsmentioning
confidence: 99%